Students’ Attitudes Towards The Implementation of WhatsApp Messenger as Online Platform in Teaching Writing - Ela Mulia Al Husna (English Research Journal : Journal of Education, Language, Literature, Arts and Culture, 2020)
This research was concerned with the students’ attitudes on the implementation of WhatsApp Messenger in teaching writing. The aim from the research are : (1) To analyze the activities are carried out in using WhatsApp messenger in the learning process at the Eighth Grade Students of SMP N 18 Surakarta in Academic Year 2019/2020, (2) To analyze the students' perceive the applications towards WhatsApp at the Eighth Grade Students of SMP N 18 Surakarta in Academic Year 2019/2020, (3) To analyze student's utilization in the use WhatsApp Messenger to teach writing the Eighth Grade Students of SMP N 18 Surakarta in Academic Year 2019/2020. In this research, the researcher used qualitative method. The source from this research are : the interview with the English teacher, the questionnaire that distribute to the research subject via google form, and document. . The result from the research were : The Activities Carried Out in Using WhatsApp Messenger was explaining the learning material and instruction by the teacher, the students used WhatsApp Messenger as communication and discussion tools, used WhatsApp Messenger to sent an assignment to the teacher. The result of students attitudes toward use WhatsApp Messenger were : students felt happy because they could finish their assignment without felt interrupted or copied by their friends, they enjoyed the learning process because could study anytime and anywhere. The students utilization in using WhatsApp Messenger were : They used WhatsApp Messenger as place to discussed with the teacher or their friends, WhatsApp Messenger as tools to discussed about writing learning material for two hours in a day, and WhatsApp Messenger as media to practice arrange a sentence in English. Keyword : WhatsApp Messenger, Teaching Writing, Students’ Attitudes, ICT